Correlation Between BMI And LH Level and LH/FSH Ratio-A Cross-Sectional Study - Parvin, Rukhsana; Ahmmad, Be Nazir; Ara, Rawshan; Begum, Monowara; Khatun, Rokeya; Rashid, Maliha (TAJ: Journal of Teachers Association, 2022)
Background: Polycystic ovarian syndrome is the most common reproductive endocrinopathy of women during their childbearing age. Elevated LH/FSH ratio, abnormally high androgen level and relatively high endogenous estrogen production are indicative of PCOS. The diagnosis of polycystic ovarian syndrome remains controversial with some considering transvaginal sonography with the combination of clinical criteria for diagnosis. In this study, we tried to determine whether there is any impact of BMI on LH or LH/FSH ratio in PCOS for better management in the future. Materials and Methods: This is a cross-sectional study. Those clinically presented as obese, hirsute, and with menstrual disturbances were non-smokers and had not been on any medications for the last three months before the study. Age groups ˂20 and ˃40 years, non-PCOS with infertility, and nonobese patients were excluded from the study. Results: Among the total 58 patients, BMI in the range of 25-28 kg/m 2 was found in the highest frequency in 44 cases (75.9%), high LH level group in 33 cases (56.9%). LH/FSH ratio ˃2 found in 27 cases (46.66%). The correlation between BMI and LH/FSH ratio showed the highest frequency in 21 cases in the BMI group (25-28kg/m 2 ) (p ˂0.009). Random LH level amplitude was found higher in low BMI (25-28kg/m 2 ) than lower in higher BMI (28-34kg/m 2 ) (p ˂0.003). Conclusion:Assessments of basal LH levels and the LH/FSH ratio in hyperandrogenic anovulatory women would be clinically meaningful when BMI is taken into account. TAJ 2022; 35: No-1: 71-76